Intensity of male‐male competition predicts morph diversity in a color polymorphic lizard. (1st July 2017) - Pérez i de Lanuza, Guillem; Carretero, Miguel A.; Font, Enrique
Abstract: Sexual selection is one of the main processes involved in the emergence and maintenance of heritable color polymorphisms in a variety of taxa. Here, we test whether the intensity of sexual selection, estimated from population sex ratio, predicts morph diversity in Podarcis muralis, a color polymorphic lizard with discrete white, yellow, orange, white‐orange, and yellow‐orange male and female phenotypes (i.e., morphs). In a sample of 116 Pyrenean populations and 5421 lizards, sex ratios (m/f) vary from 0.29 to 2.5, with the number of morphs for each sex ranging from 2 to 5. Male‐biased sex ratios are associated with increased morph diversity as measured with Shannon's diversity index. The main factor accounting for this relationship is male morph richness (i.e., the number of morphs). In contrast, female morph diversity is not related to sex ratio. These results suggest a relationship between the intensity of male intrasexual competition and male morph diversity. While other selective forces may interact with sexual selection in maintaining the color polymorphisms in P. muralis, this evidence suggests a complex evolutionary scenario possibly involving frequency‐dependent selection of alternative reproductive tactics and/or complex balancing selection.